2003
DOI: 10.3168/jds.s0022-0302(03)73931-9
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Phosphorus in Lactating Cows Fed Varying Amounts of Phosphorus and Forage

Abstract: The objective of this study was to determine the effect of dietary forage proportion and P content on fecal P excretion. Four dietary treatments were formed in a 2 x 2 factorial arrangement. The P content was 0.33 or 0.42%, and the forage proportion was 48 or 58% on a dry matter (DM) basis. The neutral detergent fiber content was 27 and 30% for the low and high forage diets, respectively. The P amount was varied by using monosodium phosphate, and the forage amount by changing the proportions of alfalfa silage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 29 publications
6
21
1
2
Order By: Relevance
“…Similarly, there were no significant differences in milk lactose, fat-corrected milk (FCM), SNF, or SCC ( P  > 0.05). These observations are consistent with previous reports in the literature [16], which indicate that varying dietary P from 0.37 to 0.57% does not affect milk composition.…”
Section: Resultssupporting
confidence: 93%
“…Similarly, there were no significant differences in milk lactose, fat-corrected milk (FCM), SNF, or SCC ( P  > 0.05). These observations are consistent with previous reports in the literature [16], which indicate that varying dietary P from 0.37 to 0.57% does not affect milk composition.…”
Section: Resultssupporting
confidence: 93%
“…A biological explanation for this result could be that absorbed P in excess of the animal's requirements is extensively recycled through saliva. It has been suggested that dietary NDF content increases salivary P secretion as a result of increased saliva flow caused by increased chewing (Khorasani et al, 1997;Wu et al, 2003), but that the effect of NDF content on salivary P secretion would likely be less at lower levels of dietary P (Wu et al, 2003). At low P intake, the animal's priority is rumen function at the expense of bone or salivary P (Puggaard et al, 2011).…”
Section: Fecal P (G/d)mentioning
confidence: 99%
“…This database subset comprised data from lactating dairy cows from 25 studies (Martz et al, 1990;Morse et al, 1992;Spiekers et al, 1993;Delaquis and Block, 1995;Khorasani et al, 1997;Knowlton et al, 2001Wu et al, 2001Wu et al, , 2003Knowlton and Herbein, 2002;Guyton et al, 2003;Kebreab et al, 2005;Kincaid et al, 2005;Shore et al, 2005;Wu, 2005;Ekelund et al, 2006;Kamiya et al, 2006a;Knowlton et al, 2007;Dann et al, 2008;Moreira et al, 2009;Myers and Beede, 2009;Taylor et al, 2009;Van Straalen et al, 2009;Herrera et al, 2010;Puggaard et al, 2011) and included 130 treatment means. The response variable of interest was P excretion in the feces, both in grams per day and as a fraction of P intake.…”
Section: Databasementioning
confidence: 99%
“…Este y otros estudios indican una relación directa entre el consumo de fósforo y su excreción. Wu et al (2003) por ejemplo, encontraron que reducir la concentración de fósforo en la dieta de 0,42 a 0,33% resultó en aproximadamente 25% menos fósforo excretado estimado en las heces. Por su parte Cerosaletti et al (2004), al implementar estrategias para disminuir el contenido de fósforo en las dietas, redujeron la excreción de este elemento en un 33%.…”
Section: El Fósforo En El Ganado De Lecheunclassified